2022
DOI: 10.3389/fmicb.2022.881442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Arbuscular Mycorrhizal Fungi Isolated From Rock Phosphate Mine and Agricultural Soil on the Improvement of Wheat Plant Growth

Abstract: The improvement of plant growth and yield becomes crucial to feed the rising world population, especially in harsh conditions, drought, salt stress, lack of nutrition, and many other challenges. To cope with these stresses, plants developed an adaptation strategy (mycorrhiza), which is an efficient way to reinforce their growth and resistance. For this purpose, we studied the influence of mycorrhizal fungi isolated from a natural rock phosphate mine in the vicinity of some native plants and agricultural soil t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…In this work, we searched for Pseudomonas adapted to a phosphate mine environment as a promising strategy. In our previous works, we showed that isolation of Bacillus strains and Mycorrhizae from this environment led to efficient growth in wheat ( Azaroual et al., 2020 ; Hazzoumi et al., 2022 ). Under semi-controlled conditions, inoculation with phosphate solubilizing bacteria Bg32c, Bg22c, and the consortium (Bg22c + Bg32c), resulted in improved growth and physiological and biochemical parameters of cherry tomato compared to the negative control.…”
Section: Discussionmentioning
confidence: 96%
“…In this work, we searched for Pseudomonas adapted to a phosphate mine environment as a promising strategy. In our previous works, we showed that isolation of Bacillus strains and Mycorrhizae from this environment led to efficient growth in wheat ( Azaroual et al., 2020 ; Hazzoumi et al., 2022 ). Under semi-controlled conditions, inoculation with phosphate solubilizing bacteria Bg32c, Bg22c, and the consortium (Bg22c + Bg32c), resulted in improved growth and physiological and biochemical parameters of cherry tomato compared to the negative control.…”
Section: Discussionmentioning
confidence: 96%